A Case of Bipolar Affective Disorder and Aspiration Pneumonia. (15th July 2013) - Gerada, Alessandro; Dell'Erba, Gaetano
Abstract : Adults with mental illness are at a higher risk of aspiration pneumonia than the general population. We describe the case of a patient with bipolar affective disorder and two separate episodes of aspiration pneumonia associated with acute mania. We propose that he had multiple predisposing factors, including hyperverbosity, sedative medications, polydipsia (psychogenic and secondary to a comorbidity of diabetes insipidus), and neuroleptic side effects.